2013
DOI: 10.1353/csd.2013.0079
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Institutional Mission on Student Volunteering

Abstract: This study examined patterns and predictors of volunteering among students at a liberal arts college with an institutional culture that strongly promotes community service. Results showed that predictors varied across four different types of volunteering: community service, social action, religious service, and service to the college. Year in school, academic performance, and familiarity with the college’s mission statement were the most consistent predictors, but only familiarity with the mission was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Their participation has also been shown to be more than fleeting, with one study finding students spent an average of 2.5 hours performing community service every week (Sullivan, Ludden, & Singleton Jr., 2013), while another found freshmen and juniors were equally willing to perform community service (Griffith, 2010). College students have also shown a willingness to volunteer in almost any community service organization setting (Astin & Sax, 1998), including education, public safety, religious-based, civic awareness, economic development, health issues, and many others Berger & Miler, 2002;.…”
Section: Community Service and College Studentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Their participation has also been shown to be more than fleeting, with one study finding students spent an average of 2.5 hours performing community service every week (Sullivan, Ludden, & Singleton Jr., 2013), while another found freshmen and juniors were equally willing to perform community service (Griffith, 2010). College students have also shown a willingness to volunteer in almost any community service organization setting (Astin & Sax, 1998), including education, public safety, religious-based, civic awareness, economic development, health issues, and many others Berger & Miler, 2002;.…”
Section: Community Service and College Studentsmentioning
confidence: 99%
“…Additionally, students attending an institution mentioning community engagement in its mission were found to be statistically more likely to perform any type of community service if they were aware of the institution's mission (Sullivan et al, 2013). While the connection between community service and the university's mission statement has a historical foundation, recent research has also found mission statements failing to mention community engagement (Weerts & Sandmann, 2008).…”
Section: Community Service and Higher Educationmentioning
confidence: 99%
See 3 more Smart Citations